PROSPEK INDUSTRI PENGOLAHAN LIMBAH SABUT KELAPA - Subiyanto (BRIN Publishing (Penerbit BRIN), 2000)
This article discusses the prospect of coco fibre industry in Indonesia as an effort of increasing added value of coconut product. Supported by the abundance and less utilization of raw materials (coco fibre) throughout the country and increasing price and demand for coco fibre products, domestically as well as internationally, Indonesia has a potential chance for promoting coco fibre based industries. The simple industry that produces coir fibre and coir dust is recommended to be built by using selected technology. Various characteristics of supporting technologies and the financial feasibility of coco fibre based industry have been the concluding remark of the discussion in this article. The industry that use the MTM1 and Bandung type machines in its process is found financially feasible.